Pembelajaran Mufrodat dengan Metode Mind Mapping: Studi Kasus di Pondok Pesantren Darul Lughah wal Quran Pamekasan Madura - Wiwik Prasetiyo Ningsih; Mohammad Zainal Hamdy; Ruji Ruji (Aqlamuna: Journal of Educational Studies, 2023)
Mastery vocabularies is the most important thing in learning Arabic. In order to mastery Arabic, students have to mastery vocabularies at first. If they have memorized a lot of vocabularies, so mastery Arabic is easy for them. But in fact, many of students are bored when practice learning vocabularies, because of focused on a complicated memorization task. Darul Lughah Wal Qur’an Islamic College is one of educational institution that use Mind Mapping method in learning vocabularies. This is a new innovation for increasing effectiveness when learning vocabularies and also for removing exhaustion. This research is Qualitative Research, which is this research aims to find a new theory. Researcher uses Analysis Descriptive Technique to analyze the data that has been collected. That is by describing a new theory about learning vocabularies with Mind Mapping method. The results of this research are 1) Mind Mapping is very effective method for teaching Arabic vocabularies which is structured designed, comes with pictures and colours, so that optimizing brain work when recording information, remembering, and calling out the information when it is needed. 2) learning vocabularies with Mind Mapping Method in Darul Lughah Wal Qur’an Islamic College is joyfull. And this method is very effective to help the students memorizing and mastering the vocabularies